Reliability Analysis on the Effect of Subsea Buoy to the Tension of Spread Mooring System - Silfiani, Madea Eka; Prastianto, Rudi Walujo; Prastianto, Murdjito; Rosyid, Daniel Mohammad; Djatmiko, Eko Budi (International Journal of Marine Engineering Innovation and Research, 2025)
A lot of research has been carried out regarding variations in mooring systems, one of which is the addition of buoys to the mooring system. In analyzing variations in mooring system designs, what needs to be considered is the reliability of the mooring lines. Therefore, in this research will analyze reliability on the effect of subsea buoy to the tension of mooring line with a variation position of subsea buoy. The variations on the position of one subsea buoy is arranged at the distance of the anchor 605 m, 577.5 m, 550 m, 522.5 and two subsea buoys at the distance from the anchor 605 m and 467.5 m. The analysis was performed for stand alone and offloading conditions with wave directions of 0 °, 45 °, 90 °, 135 °, 180 °. In this study to find the reliability of mooring lines, the author uses the Mean Value First Order Second Moment (MVFOSM) method. The results from this study, the probability of failure in the offloading condition without subsea buoy is 4.897E-17 and with subsea buoy (522.5 m) is 4.018E-17. Probability of failure in the stand alone condition without subsea buoy is 2.763E-16 and with subsea buoy (522.5 m) is 1.881E-16. From the probability of failure, the reliability of mooring lines in the offloading condition and stand alone condition without subsea buoy and with subsea buoy (522.5 m) is 1.00. The reliability calculation determined by DNV-OS E301, the results obtained meet the specified reliability criteria.